Buckling Response Analysis of Laminated Plates Subjected to Localised Bi-axial In-plane Compressive Loading. Issue 1 (December 2020) - Lal, Achchhe; Parghi, Anant; Mahto, Anil Kumar; Kumar, Rahul
Abstract: Laminated composite plates are well known structural member since last four decades because of its high stiffness and strength to weight ratio. Usually this type of structural members is subjected to partial biaxial loading during their functioning. For better safety and stability of structure, analysis of these structural member in that condition of loading is necessary. In this present analysis buckling response of laminated composite plates under biaxial partial in-plane loading is examined and effect of various parameters like aspect ratio, stacking sequence, fiber orientation and plate thickness ratio of nondimensionalised critical buckling load (NCBL) are revealed. A MATLAB program is developed higher order shear deformation theory based on finite element method for buckling analysis of laminated composite plate. Efficiency of the program is checked by comparing the result of the present work with that of already published which shows good favour of later one.